속방형 및 용출조절형 비타민 C 정제의 용출 특성 비교 분석 - 양효진; 류나희; 양주홍; 홍선호; 이연경; 조양희; Yang, Hyo-Jin; Ryu, Na-Hee; Yang, Joo-Hong; Hong, Sun-Ho; Lee, Yeonkyung; Cho, Yang-Hee (Han'gug sigpum wi'saeng anjeonseong haghoeji, 2022)
In this study, a comparative dissolution experiment was conducted between an immediate-release and a controlled-release vitamin C tablet applied with a technology to control the dissolution of vitamin C to maintain the vitamin C level in the human body. In order to confirm the dissolution rate (%) of vitamin C tablets, HPLC determination was conducted based on the dissolution test methods in the 'Korean Pharmacopoeia (No. 2020-88),' 'Guidelines on Specifications of Dissolution Tests for Oral dosage Forms,' and 'Standard and Specifications for Health Functional Foods (No. 2020-63)' from Ministry of Food and Drug Safety (MFDS). In addition, the dissolution pattern between the immediate-release tablet and the controlled-release tablet was comparatively analyzed. The analysis result confirmed that the immediate-release vitamin C tablet was 100% dissolved after 45 minutes, while the controlled-release vitamin C tablet was 100% dissolved after 480 minutes (8 hours). Furthermore, the dissolution rate (%) at 60 minutes was slower than that of the immediate-release vitamin C tablet. Based on these results, this study confirmed that the dissolution rate (%) test and development of controlled-release tablets containing vitamin C as the main component a re possible. 본 연구에서는 체내에서 비타민 C의 지속성을 나타내기 위해 성분의 용출을 조절하는 기술이 적용된 용출조절형 비타민 C 제품과 일반적인 속방형 비타민 C 제품의 비교용출 실험을 진행하여, 일반적인 속방형 제품과 용출조절형 제품 간의 용출 양태를 비교분석 하였다. 비타민 C 정제들의 용출률을 확인하기 위해 '대한약전(제2020-88호)', '경구용의약품의 용출규격 설정 가이드라인'의 용출시험법, '건강기능식품의 기준 및 규격 고시(제2020-63호)'에 근거한 HPLC 함량시험을 수행하여 시간별 용출률을 분석하였다. 분석 결과 속방형 비타민 C 제품은 45분 이후 100% 용출이 이루어진 반면 용출조절형 비타민 C 제품은 480분(8시간) 이후에 100% 용출이 나타났으며, 용출조절형 비타민 C 제품의 60분에서의 용출률이 속방형 비타민 C 제품에 비해 더 느리게 나타나는 것을 확인하였다. 이러한 결과를 바탕으로 비타민 C를 주성분으로 한 용출조절형 정제의 개발 및 용출분석이 가능함을 확인하였다.